Pioneering Change: Women’s Economic Empowerment under Saudi Vision 2030 - Jamilah, Maryam; Isnarti, Rika (Sawwa: Jurnal Studi Gender, 2024)
Women's empowerment efforts always encounter obstacles and challenges. This paper explores the economic empowerment of women in Saudi Arabia within the context of Saudi Vision 2030, a plan aimed at enhancing women's roles in various sectors. Although existing research has addressed women’s empowerment under this vision, a comprehensive evaluation of the government’s initiatives is still lacking. The study evaluates policies designed to economically empower women, guided by a theoretical framework based on key empowerment elements: agency, access to resources, opportunity structure, and achievement, inspired by the perspectives of Evelyn Derera and Amartya Sen. A qualitative, descriptive approach is used, incorporating secondary data analysis from literature reviews and government reports on Vision 2030. Findings reveal that reforms have increased women’s participation in economic and educational sectors, including partial removal of the male guardianship system. However, challenges such as cultural norms, nepotism, and gender discrimination continue to limit women’s access to higher leadership roles. Despite significant progress, more efforts are required to address these persistent barriers and fully empower women in Saudi Arabia.